The use of 2-D speckle tracking echocardiography in assessing adolescent athletes with left ventricular hypertrabeculation meeting the criteria for left ventricular non-compaction cardiomyopathy. (15th January 2023) - Dorobantu, Dan M.; Radulescu, Cristina R.; Riding, Nathan; McClean, Gavin; de la Garza, María-Sanz; Abuli-Lluch, Marc; Duarte, Nuno; Adamuz, Maria Carmen; Ryding, Diane; Perry, Dave; McNally, Steve; Stuart, A. Graham; et al.
Abstract: Background: Current echocardiographic criteria cannot accurately differentiate exercise induced left ventricular (LV) hypertrabeculation in athletes from LV non-compaction cardiomyopathy (LVNC). This study aims to evaluate the role of speckle tracking echocardiography (STE) in characterising LV myocardial mechanics in healthy adolescent athletes with and without LVNC echocardiographic criteria. Methods: Adolescent athletes evaluated at three sports academies between 2014 and 2019 were considered for this observational study. Those meeting the Jenni criteria for LVNC (end-systolic non-compacted/compacted myocardium ratio > 2 in any short axis segment) were considered LVNC+ and the rest LVNC-. Peak systolic LV longitudinal strain (Sl ), circumferential strain (Sc ), rotation (Rot), corresponding strain rates (SRl/c ) and segmental values were calculated and compared using a non-inferiority approach. Results: A total of 417 participants were included, mean age 14.5 ± 1.7 years, of which 6.5% were LVNC+ ( n  = 27). None of the athletes showed any additional LVNC clinical criteria. All average Sl, SRl Sc, SRc and Rot values were no worse in the LVNC+ group compared to LVNC- ( p values range 0.0003–0.06), apart from apical SRc ( p  = 0.2). All 54 segmental measurements (Sl /Sc SRl /SRc and Rot) had numerically comparable means in both LVNC+ and LVNC-, of which 69% were also statistically non-inferior. Conclusions: Among healthy adolescent athletes, 6.5% met the echocardiographic criteria for LVNC, but showed normal LV STE parameters, in contrast to available data on paediatric LVNC describing abnormal myocardial function. STE could better characterise the myocardial mechanics of athletes with LV hypertrabeculation, thus allowing the transition from structural to functional LVNC diagnosis, especially in suspected physiological remodelling. Graphical abstract: The use of 2D speckle tracking echocardiography in athlete assessment. Unlabelled Image Highlights: Even among healthy adolescent athletes, 6.5% meet echocardiographic criteria for left ventricular non-compaction. These athletes have normal global and segmental myocardial mechanics despite apparent significantly remodelled LV. Adding speckle tracking echocardiography to current criteria could improve screening in athletes with LV hypertrabeculation.